PERAN KATEKIS MELALUI KATEKESE KEBANGSAAN DEMI TERCIPTANYA PARTISIPASI UMAT KATOLIK DALAM KEHIDUPAN BERBANGSA - Vinsensius Rixnaldi Masut (Al Hikmah, 2023)
This paper focuses on revealing the important role of catechists endowed with a spirit of nationalism in building the lives of grassroots Catholics. Its motivation is the fact that grassroots Catholics behave passively and apathetically in social life. They are more likely to actively build fellowship within (the Church) and neglect fellowship outwards (society) with other groups. Therefore, a nationalistic catechesis is needed, carried out by catechists. It must be an elaboration of Christian spirituality with the values of Pancasila. The Indonesian Catholic Church in its long history has always supported and practiced the values of Pancasila in its mission. The methodology used in writing this academic paper is library research. The author performed a critical reading of news items in HIDUP magazine, relating them to Church teaching or other books connected with the theme of this academic work. The conclusion of this paper is that grassroots Catholics â€œare presentâ€ together with other groups in order to actively participate in building this nation.